Prognostic Impact of the Symptom of New-Onset Atrial Fibrillation in Acute Myocardial Infarction: Insights From the NOAFCAMI-SH Registry - Luo, Jiachen; Liu, Baoxin; Li, Hongqiang; Xu, Siling; Gong, Mengmeng; Li, Zhiqiang; Qin, Xiaoming; Shi, Beibei; Hao, Chuanzhen; Zhang, Ji; Wei, Yidong (Frontiers in Cardiovascular Medicine, 2021)
ABSTRACT Background: New-onset atrial fibrillation (NOAF) is a common complication during acute myocardial infarction (AMI) and sometimes can be completely asymptomatic, but the clinical implications of these asymptomatic episodes require further characterization. The objective of this study was to investigate the short- and long-term prognostic impact of post-MI NOAF based on the presence of AF-related symptoms. Methods: The NOAFCAMI-SH registry was a retrospective cohort including participants with AMI without a documented history of AF. Patients with NOAF were divided into 2 groups according to the AF-related symptoms. The primary endpoint was all-cause mortality. Results: Of 2399 patients included, 278 (11.6%) developed NOAF of whom 145 (6.0%) with asymptomatic episodes and 133 (5.5%) with symptomatic ones. During hospitalization, 148 patients died (106, 10, and 32 in the sinus rhythm [SR], asymptomatic, and symptomatic NOAF groups, respectively). After multivariable adjustment, only symptomatic NOAF was associated with in-hospital mortality (odds ratio [OR]: 2.32, 95% confidence interval [CI]: 1.36-3.94) compared with SR. Over a median follow-up of 2.7 years, all-cause mortality was 3.2%, 12.4%, and 11.8% per year in the SR, asymptomatic, and symptomatic NOAF groups, respectively. After adjustment for confounders, it was the asymptomatic NOAF (hazard ratio [HR]: 1.61, 95%CI: 1.09-2.37) rather than the symptomatic one (HR: 1.37, 95%CI: 0.88-2.12) that was significantly related to mortality. Similar results were also observed for cardiovascular mortality (HRs and 95%CI were 1.71 [1.10-2.67] and 1.25 [0.74-2.11] for asymptomatic and symptomatic NOAF, respectively). Both asymptomatic and symptomatic NOAF episodes were associated with heart failure, whereas only those with symptomatic NOAF were at heightened risk of ischemic stroke. Our exploratory analysis further identified patients with asymptomatic high-burden NOAF as the highest-risk population (mortality: 19.6% per year). Conclusion： Among patients with AMI, symptomatic NOAF is related to in-hospital mortality and asymptomatic NOAF is associated with poor long-term survival.